The Effect of Brand Personality in Building Customer Loyalty in Umrah Travel Services through Brand Trust - Siti Afin Nur Fitriana; Astrid Puspaningrum; Raditha Dwi Vata Hapsari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The increasing enthusiasm of Indonesian Muslims to perform umrah has intensified competition among travel agencies, creating a growing need to understand the factors that shape customer loyalty in this service-based industry. Although prior studies have examined determinants of loyalty, limited research integrates brand personality and brand trust specifically within repeated umrah travel experiences, indicating a clear research gap. This study aims to develop hypotheses regarding the factors influencing brand loyalty, with a particular focus on the effect of brand personality mediated by brand trust. This study also addresses how perceptions of competence, sincerity, and enthusiasm as dimensions of brand personality contribute to customer loyalty. Using a quantitative approach, data were collected from 127 umrah pilgrims who had used the same travel agency more than once during the 2022–2024 period, selected through saturated sampling and analyzed using PLS-SEM. The findings reveal that brand personality significantly enhances brand loyalty, while brand trust acts as a mediating mechanism that strengthens this relationship. Trust functions as a psychological bridge that connects perceived brand characteristics with the decision to remain loyal. The study highlights the importance for Umrah travel providers to cultivate trustworthy and compelling brand identities to maintain customer confidence and long-term loyalty. Keywords: brand personality, brand trust, brand loyalty